Programming SQL Server 2005 - Hamilton, Bill (O'Reilly, 2006)
SQL Server 2005, Microsoft's next-generation data management and analysis solution, represents a huge leap forward. It comes with a myriad of changes that deliver increased security, scalability, and power--making it the complete data package. Used properly, SQL Server 2005 can help organizations of all sizes meet their data challenges head on. Programming SQL Server 2005 from O'Reilly provides a practical look at this updated version of Microsoft's premier database product. It guides you through all the new features, explaining how they work and how to use them. The first half of the book examines the changes and new features of the SQL Server Engine itself. The second addresses the enhanced features and tools of the platform, including the new services blended into this popular version. Each chapter contains numerous code samples-written in C♯ and compiled using the Visual Studio 2005 development environment-that show you exactly how to program SQL Server 2005. Programming SQL Server 2005 can help you: Build, deploy, and manage enterprise applications that are more secure, scalable, and reliable Maximize IT productivity by reducing the complexity of building, deploying, and managing database applications Share data across multiple platforms, applications, and devices to make it easier to connect internal and external systems Because the goal of Programming SQL Server 2005 is to introduce all facets of Programming SQL Server 2005, it's beneficial to programmers of all levels. The book can be used as a primer by developers with little experience with SQL Server, as a ramp up to the new programming models for SQL Server 2005 for more experienced programmers, or as background and primer to specific concepts. Any IT professional who wants to learn about SQL Server 2005's comprehensive feature set, interoperability with existing systems, and automation of routine tasks will find the answers in this authoritative guide.